Quantifying aerosol and microbial exposure of healthcare workers in endoscopy suites: a time-based study - Ye, Meng Dan; Li, Ning Ning; Li, Wen; Wu, Qi Han; Wang, Ying Ying; Li, Bing Ru; Sheng, Yuan (Frontiers in Public Health, 2025)
ObjectivesThis study aimed to quantify aerosol and microbial exposure levels during different working hours, analyze temporal air pollution trends in the endoscopy suite, and provide evidence to optimize infection prevention strategies.MethodsA portable laser particle counter and an airborne bacteria sampler were used to measure aerosol particle concentrations and microbial loads at four time points: before the commencement of work (baseline), and 1, 2, and 3 h after work initiation. Continuous data collection was conducted over 10 consecutive working days. Air quality assessments were performed through scientific evaluation according to relevant international and national standards.ResultsQualified rates for aerosols ≥0.5 μm increased by 20–30% during the 3 working hours compared to baseline levels. Microbial qualified rates remained at 100% throughout the study period. Aerosol concentrations across all particle sizes significantly increased with working hours (p < 0.01). The growth rate of 5–10 μm aerosols was higher than that of 0.3–5 μm particles (p < 0.01). After 3 h, concentrations of 0.5–25 μm and 0.3–10 μm aerosols increased by 1.48-fold and 1.3-fold compared to baseline values. Total microbial colonies positively correlated with work duration, polyp detection frequency, biopsy procedures performed, and procedure duration (p < 0.05). Microbial analysis identified 12 species, predominantly bacteria (79.6%) and fungi (20.4%).ConclusionThis study highlights trends in aerosol and microbial contamination over time and identifies four factors influencing microbial counts in the endoscopy suite. We propose some recommendations to reduce exposure risks for HCWs and patients.